1996
DOI: 10.1002/(sici)1097-4628(19960627)60:13<2489::aid-app19>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated clinical fabrication heat treatment and artificial weathering on the tensile testing of prosthetics/orthotics polymers

Abstract: SYNOPSISThe tensile behavior was compared for five prosthetics/orthotics polymers: Durr-Plex (copolyester), Polypropylene (polypropylene), Subortholen (polyethylene), Surlyn (ionomer), and Uvex (and cellulose acetate butyrate). Tensile properties, yield strength, and modulus of elasticity are related to a number of factors including composition and condition of polymers. The polymers were examined in the as-received and simulated clinical fabrication heat-treated conditions. The simulated clinical fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…For good clamping, the ends of the fiber specimens were glued to cardboard frames with epoxy resin [10]. The tensile modulus was determined from the initial linear slope of the stress-strain curve [ 16].…”
Section: Measurement Of Physical Propertiesmentioning
confidence: 99%
“…For good clamping, the ends of the fiber specimens were glued to cardboard frames with epoxy resin [10]. The tensile modulus was determined from the initial linear slope of the stress-strain curve [ 16].…”
Section: Measurement Of Physical Propertiesmentioning
confidence: 99%
“…Many commercial products were compared. Studies performed elsewhere [331][332][333] showed only marginal changes of prosthetic materials exposed in QUV. It is not clear what might be the contribution of the UV curing process because such study was not done.…”
Section: Dental Materialsmentioning
confidence: 94%